Ohvira syndrome with left radial hemimelia: a rare association - T., Jayanthy; Rao, Rachana B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Ohvira syndrome is rare complex anomaly consisting of uterus didelphys, unilateral ipsilateral obstructed hemivagina and ipsilateral renal agenesis. It typically presents with dysmenorrhea or pelvic pain shortly after menarche due to collection of secretions in the uterus. Reporting a case of 32 years unmarried nulligravida lady with complaints of pain abdomen since 20 days with history of similar complaints 15 years bac. Patient was on Inj. DMPA 2 years back. On examination upper limb skeletal deformity-left radial hemimelia present with a mass of 14-16 weeks gravid uterus on per abdomen examination. USG (February 2020), was suggestive of uterus didelphys bicollis with collection of 108 cc noted in the right uterine cavity with right kidney agenesis with obscured right ovary. Total abdominal hysterectomy with left salphingo-oopherectomy was done. Specimen features were suggestive of uterus didelphys bicornis bicollis with right uterus hematometra with right cervix blind with right sided blind vagina with features suggestive of Ohvira syndrome.